ANALISIS VARIASI BENTUK NOZZLE PIPIH DAN BULAT TERHADAP PUTARAN TURBIN DAN GENERATOR PADA PROTOTYPE PLTSa - Kalimullah, Muhammad; Indra Partha, Cok Gede; Sukerayasa, I Wayan (Jurnal SPEKTRUM; Vol 12 No 1 (2025): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2025.v12.i01.p6, 2025)
Waste is a problem that is still difficult to overcome. In 2023 in Bali Province the amount of waste produced will reach 1,027,433.75 tons per year. Badung Regency is one of the largest waste suppliers in Bali Province. In Badung Regency, the waste produced reaches 195,222.46 tons per year. TPST 3R Legian Kaja is a waste management facility located in Badung Regency. This TPST is capable of managing 16 tons of waste per day, one of the methods used is incineration or burning of waste. During the combustion process, the heat energy produced can actually be used to produce electrical energy. However, most of the heat energy produced is not utilized, so there is the potential for wasting heat energy. This research aims to design and create a prototype waste-powered power plant as an energy and waste management solution. The method used in this research is descriptive quantitative. This research uses a variety of flat and round nozzle shapes to obtain optimal turbine rotation. This test showed that the highest turbine rotation occurred in the flat nozzle shape, which resulted in a turbine rotation of 1179 RPM before being coupled to the generator and 922 RPM after being coupled to the generator.